Morphine infusions into the rostrolateral periaqueductal gray affect maternal behaviors - L.M. Moura; N.S. Canteras; M.H. Sukikara; L.F. Felicio (Brazilian Journal of Medical and Biological Research, 2010)
It is well established that morphine inhibits maternal behaviors. Previous studies by our group have shown activation of the rostrolateral periaqueductal gray (rlPAG) upon inhibition-intended subcutaneous injections of morphine. In this context, we demonstrated that a single naloxone infusion into the rlPAG, following this opioid-induced inhibition, reactivated maternal behaviors. Since these data were obtained by using peripheral morphine injections, the present study was designed to test whether morphine injected directly into the rlPAG would affect maternal behaviors. Our hypothesis that morphine acting through the rlPAG would disrupt maternal behaviors was confirmed with a local infusion of morphine. The mothers showed shorter latency for locomotor behavior to explore the home cage (P = 0.049). Inhibition was especially evident regarding retrieving (P = 0.002), nest building (P = 0.05) and full maternal behavior (P = 0.023). These results support the view that opioidergic transmission plays a behaviorally meaningful inhibitory role in the rostrolateral PAG.